Insecure Property Rights and the Missing Middle - Aram Grigoryan; Mattias Polborn (Center for Economic Studies and ifo Institute (CESifo), 2018)
We analyze a theoretical model in which entrepreneurs' property rights are threatened by “raiders” who can challenge them to a contest for control of their firms. Entrepreneurs have heterogeneous productivity, and decide how much capital to invest before raiders decide whom to attack. In equilibrium, low productivity entrepreneurs are unaffected by the existence of raiders, while mid- and high-productivity entrepreneurs suffer. However, while raiders essentially act like a tax for the highest productivity entrepreneurs, the investment behavior of mid-productivity entrepreneurs who try to avoid an attack is more drastically affected. Our model provides a novel theoretical explanation for the “missing middle” observed in many countries with insecure property rights.
Keywords: 330; property rights; rent-seeking; corruption; missing middle